2015
DOI: 10.1002/bdm.1902
|View full text |Cite
|
Sign up to set email alerts
|

How Information Availability Interacts with Visual Attention during Judgment and Decision Tasks

Abstract: Decisions in front of a supermarket shelf probably involve a mix of visually available information and associated memories—and interactions between those two. Several cognitive processes, such as decision making, search, and various judgments, are therefore likely to co‐occur, and each process will influence visual attention. We conducted two eye‐tracking experiments capturing parts of these features by having participants make either judgments or decisions concerning products that had been previously encoded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Clarifying aspects of brain circuitry by illustrating the complex interplay between vision and cognition, 62 eye movement measurements are actively performed in interdisciplinary laboratories that integrate contributions from psychology, neuroscience, economy, philosophy and computer science. A vast number of efficient and well‐grounded behavioral experimental paradigms have been generated regarding sincerity, 63 magic‐tricks, 64, 65 judgmental tasks, 66–71 moral dilemma, 72 reading, 73–76 visual search, 77–79 gambling, 80 daily‐life activities, 81–86 problem‐solving, 39, 87–89 learning 90 and discrete choice in clinical decision‐making 91 . Vision science becomes actively adopted in neuromarketing, aiming to reveal valuable information about consumers’ decisions, as well as answer the question of how to hack the consumer's internal ‘purchase button’ 92–96 …”
Section: Vision Science As a New Practicementioning
confidence: 99%
“…Clarifying aspects of brain circuitry by illustrating the complex interplay between vision and cognition, 62 eye movement measurements are actively performed in interdisciplinary laboratories that integrate contributions from psychology, neuroscience, economy, philosophy and computer science. A vast number of efficient and well‐grounded behavioral experimental paradigms have been generated regarding sincerity, 63 magic‐tricks, 64, 65 judgmental tasks, 66–71 moral dilemma, 72 reading, 73–76 visual search, 77–79 gambling, 80 daily‐life activities, 81–86 problem‐solving, 39, 87–89 learning 90 and discrete choice in clinical decision‐making 91 . Vision science becomes actively adopted in neuromarketing, aiming to reveal valuable information about consumers’ decisions, as well as answer the question of how to hack the consumer's internal ‘purchase button’ 92–96 …”
Section: Vision Science As a New Practicementioning
confidence: 99%
“…Before consumers decide to purchase a food product, they normally look at the product they are going to purchase; thus, visual attention usually precedes the purchase decision [49,50,51,52]. Previous research has shown that visual attention influences food choice, in that the more visual attention a package or a certain label on a package receives, the more likely it is that this product will be chosen [44,51,52,53,54,55,56,57]. The eye movements, and consequently the visual attention to stimuli, can be measured with an eye tracking device.…”
Section: Introductionmentioning
confidence: 99%
“…Tracking the gaze provides a moment-by-moment assessment of thought processes in a wide variety of contexts ( Shepherd et al, 1986 ; Liversedge and Findlay, 2000 ; Theeuwes et al, 2009 ; Tatler et al, 2010 ; Bulling et al, 2011 ). Visual behavior is tightly linked to learning ( Heisz and Shore, 2008 ), associative memory ( Hannula and Ranganath, 2009 ), saliency determination ( Henderson, 2003 ), judgment tasks concerning products ( Pärnamets et al, 2016 ), decision-making under uncertainty ( Zommara et al, 2018 ), and moral dilemma problem solving ( Pärnamets et al, 2015 ). Particularly gaze duration, or viewing time, appears to be a useful index of the extent of information processing (see Lauwereyns, 2012 , for a comprehensive review).…”
Section: Introductionmentioning
confidence: 99%